ANALISIS KEPATUHAN WAJIB PAJAK BEA PEROLEHAN HAK ATAS TANAH DAN ATAU BANGUNAN DALAM MENINGKATKAN PENERIMAAN PAJAK PADA BADAN PENDAPATAN DAERAH - Reka TiaVinola IfaniSari; Kurnia Krisna Hari; Aprianto Aprianto (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This research was conducted to answer the existing problem, namely how taxpayer compliance with land and/or building rights acquisition fees (BPHTB) increases tax revenue at regional revenue bodies. The aim is to determine taxpayer compliance with fees for acquiring land and/or building rights in order to increase tax revenues to regional revenue bodies. This research uses descriptive research. The location of the research was the Regional Revenue Agency of Penukal Abab Lematang Ilir Regency, South Sumatra Province. The operational variable used is taxpayer compliance. The data used in this research are primary and secondary data. The data collection method used in this research is observation and interviews. The data analysis technique used in this research is to describe and explain how taxpayer compliance with fees for acquiring land and/or building rights increases tax revenues at regional revenue institutions. The results of the research show that BPHTB revenue has not reached the predetermined target, this shows that taxpayer compliance in Penukal Abab Lematang Ilir Regency has not yet complied with tax obligations.